Manufactured silver nanoparticles of different sizes induced DNA strand breaks and oxidative DNA damage in hepatoma and leukaemia cells and in dermal and pulmonary fibroblasts - Ávalos, A; Haza, A. I; Morales, P (Folia biologica (Praha), 2015)
Many classes of silver nanoparticles (AgNPs) have been synthesized and widely applied, but no conclusive information on their potential cytotoxicity and genotoxicity mechanisms is available. Therefore, the purpose of this study was to compare the potential genotoxic effects (DNA strand breaks and oxidative DNA damage) of 4.7 nm coated and 42 nm uncoated AgNPs, using the comet assay, in four relevant human cell lines (hepatoma, leukaemia, and dermal and pulmonary fibroblasts) in order to understand the impact of such nanomaterials on cellular DNA. The results indicated that in all cell lines tested, 4.7 nm coated (0.1-1.6 μg ml⁻¹) and 42 nm uncoated (0.1-6.7 μg ml⁻¹) AgNPs increased DNA strand breaks in a dose- and size-dependent manner following 24 h treatment, the smaller AgNPs being more genotoxic. Human pulmonary fibroblasts showed the highest sensitivity to the AgNPs. A modified comet assay using endonuclease III and formamidopyrimidine- DNA glycosylase restriction enzymes showed that in tumoral and normal human dermal fibroblasts, pyrimidines and purines were oxidatively damaged by both AgNPs, but the damage was not size-dependent. However, in human pulmonary fibroblasts, no oxidative damage was observed after treatment with 42 nm AgNPs. In conclusion, both AgNP sizes induced DNA damage in human cells, and this damage could be related to oxidative stress.
Keywords: Metal Nanoparticles; dvouřetězcové zlomy DNA; Silver; velikost částic; oxidace-redukce; lidé; kovové nanočástice; Liver Neoplasms; fibroblasty; Lung; DNA Breaks, Double-Stranded; nádory jater; plíce; Oxidation-Reduction; hepatocelulární karcinom; Cell Line; Fibroblasts; Humans; buněčné linie; Carcinoma, Hepatocellular; škára; Particle Size; leukemie; Dermis; stříbro; Leukemia